Mudanças estruturais na sucessão de florestas secundárias fertilizadas por fósforo e com histórico de pastagem na Amazônia central - Souza, Marcelle São Pedro Abdiel de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2019)
Secondary forests with pasture history are regenerating in soils degraded by the intensive use of fire as a pasture management technique and by compaction caused by cattle trampling. The nutritional limitation, mainly for P, reported in great part of the soils of the Amazon Basin, can be aggravated by this type of soil use and, consequently, affect the natural regeneration after the abandonment of the area. Therefore, the main objective of this study was to analyze whether phosphate fertilization and soil acidity correction affect the structural characteristics of secondary forests in a chronosequence (different initial ages) with pasture history in central Amazonia. Ten secondary forests were fertilized in 2000, with four treatments each: phosphorus, phosphorus + liming, phosphorus + liming + gypsum and an unfertilized control. Five censuses were carried out between 2001 and 2005, the last one being in 2018, for calculation of aboveground biomass, stem density and individual mass average. Aboveground biomass stock and average individual mass of older forests increased during the successional trajectory in the control treatment, with no significant difference between P fertilization and control. In forests fertilized by P + Ca, the aboveground biomass stock decreased over time while the average individual mass increased. In forests fertilized by P + Ca + G, both aboveground biomass stock and average individual mass decreased over time. Fertilization did not affect stem density, which decreases during the successional trajectory. These results suggest a possible allocation of growth to belowground biomass and effect of phosphate fertilization and correction of soil acidity on the dynamics and floristic composition of secondary forests with pasture history.
Structural changes in succession of phosphorus-fertilized secondary forests with pasture history in central Amazonia
Keywords: Secondary forests; Pasture; Aboveground biomass; Florestas secundárias; Pastagens; Biomassa acima do sol; Limitação por P; Densidade de caules; Calagem; Limitation by P; Sstems density